Case of early-stage gastric cancer identified in the gastric mucosa with lanthanum phosphate deposition - Takatsuna, Masafumi; Takeuchi, Manabu; Usuda, Hiroyuki; Terai, Shuji (Endoscopy International Open, 2019)
Background and study aims A 78-year-old man with Helicobacter pylori infection had been undergoing hemodialysis for chronic renal failure and receiving lanthanum carbonate preparations for 3 years. Endoscopy revealed fine white granular discoloration throughout the stomach, a moderately reddish depression on the lesser curvature of the gastric angle, and white granular discoloration in the surrounding area. A magnified image using narrow-band imaging showed that the depressed part had irregular vascular and pit structures. We established a diagnosis of intramucosal gastric cancer and performed endoscopic submucosal dissection. Histopathological examination revealed a well-differentiated adenocarcinoma that was confined to the mucosa of the depressed area. Moreover, using an electron probe microanalyzer-equipped electron microscope, we found that the degree of lanthanum deposition was lower in the tumor region than in the non-tumor region. Thus, the current case can help in understanding the relationship between lanthanum deposition and early-stage gastric cancer. Because gastric cancers can occur in lanthanum deposit-containing mucosa, esophagogastroduodenoscopy should be used carefully after understanding the characteristics of early- stage gastric cancer in such cases.